2018
DOI: 10.1080/15384101.2018.1534510
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of lncRNA KCNQ1OT1 suppresses the adipogenic and osteogenic differentiation of tendon stem cell via downregulating miR-138 target genes PPARγ and RUNX2

Abstract: The study aimed to investigate the mechanism and biological roles of long noncoding RNA KCNQ1OT1 in adipogenic and osteogenic differentiation of tendon stem cell. In this study, tendon injury mice model was established to detect the expression of lncRNA KCNQ1OT1, miR-138, peroxisome proliferator-activated receptor gamma (PPARγ) and runt-related gene 2 (RUNX2) using quantitative real-time PCR (qRT-PCR) and western blot. Mechanical testing was carried out to assess tendon function. Adiponectin and Osterix were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 24 publications
(27 reference statements)
0
26
0
Order By: Relevance
“…Interestingly, dysregulation of miR-138 has also been observed in stem cells from injury tissue. Yu, et al15 proposed that the expression of miR-138 is attenuated in tendon stem cells from injured mice and that miR-138 may mediate the anti-adipogenic differentiation function of lncRNA KCNQ1OT1 knockdown by targeting PPARγ. Moreover, Nardelli, et al21 indicated that miR-138 together with miR-222-3p is overexpressed in hAMSCs from obese-pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, dysregulation of miR-138 has also been observed in stem cells from injury tissue. Yu, et al15 proposed that the expression of miR-138 is attenuated in tendon stem cells from injured mice and that miR-138 may mediate the anti-adipogenic differentiation function of lncRNA KCNQ1OT1 knockdown by targeting PPARγ. Moreover, Nardelli, et al21 indicated that miR-138 together with miR-222-3p is overexpressed in hAMSCs from obese-pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that various miRNAs affect adipogenesis by targeting several adipogenic transcription factors and key signaling molecules in vivo and in vitro 59. Among them, PPARγ is an important regulator of adipogenic differentiation and is targeted by several miRNAs, such as miR-27a/b, miR-130, and miR-138 15202223. The adipogenic commitment of tendon stem cells was suppressed by lncRNA KCNQ1OT1 knockdown via downregulating miR-138-targeted PPARγ, accompanying a loss of the adipogenic marker gene adiponectin 15.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instances of ceRNA crosstalk were experimentally tested in a very large number of contexts and were observed in both normal and pathological backgrounds, demonstrating the wide spread proliferation of the mechanism. In particular, researchers collected evidence from normal physiology, for instance in brain architecture [ 86 ] and regeneration mechanisms [ 87 ], neuronal and muscle developmental processes [ 50 , 88 ], cellular differentiation [ 89 ] and reprogramming [ 90 , 91 ] and from the immense landscape of diseases, syndromes and disorders where highly complex gene regulation circuits are most affected by perturbations. Researchers work hard to model these regulatory networks in order to predict and understand how modifications could alter the dynamic balance among molecules, causing illness such as the onset of cancer and its progression, cardiovascular problems and neurodegenerative disorders and other pathologies, such as those relating to the immune and autoimmune response and to degenerative physical condition.…”
Section: Cerna and Diseasesmentioning
confidence: 99%